OP0014 COMPARISON OF ANTERIOR UVEITIS OCCURRENCE DURING TREATMENT WITH SECUKINUMAB, ADALIMUMAB, INFLIXIMAB AND ETANERCEPT IN SPONDYLOARTHRITIS. (2nd June 2020) - Lindström, U.; Bengtsson, K.; Olofsson, T.; Di Giuseppe, D.; Glintborg, B.; Forsblad-D'elia, H.; Jacobsson, L. T. H.; Askling, J.
Abstract : Background: Randomized controlled trials indicate that compared to tumor necrosis factor inhibitors (TNFi), secukinumab (SEC) has similar efficacy regarding axial inflammation in spondyloarthritis (SpA), better efficacy regarding cutaneous psoriasis, but is inferior in inflammatory bowel disease (IBD). However, the efficacy of SEC compared to TNFi in anterior uveitis (AU) has not been extensively studied. Objectives: To compare the occurrence of AU in patients with SpA treated with SEC, adalimumab (ADA), infliximab (IFX) or etanercept (ETN), in clinical practice. Methods: Patients with ankylosing spondylitis or undifferentiated SpA starting either SEC, ADA, IFX or ETN, in 2015 through 2017, were identified in the Swedish Rheumatology Quality register, and were linked to the national patient register for identification of AU. AU-flares were defined as the number of visits with an AU diagnosis, separated by a ≥60 days penalty interval, within ophthalmology outpatient care, during the respective bDMARD treatment. Follow-up started at the bDMARD initiation, and ended at the first of Dec 31 st 2017, death, emigration or discontinuation date of the bDMARD. To assess and accommodate treatment channeling, crude incidence rates for AU-flares were determined (A) for all bDMARD treatment starts, (B) excluding patients with an AU diagnosis during the year prior to the bDMARD start, and (C) in addition, excluding all first line bDMARD treatment starts. Hazard ratios (HR) for time until a first on-treatment AU diagnosis were estimated using Cox regression (ADA=reference), adjusted for sex, age, and any history of AU, and estimating robust confidence intervals to account for the individuals contributing multiple lines of treatment. Results: In total, 2, 684 patients (52% women) contributed 3, 255 treatment initiations. SEC was less frequently used as first line bDMARD and there was channeling of patients with previous AU, towards treatment with ADA, and away from ETN (Table 1 ). Further, AU occurred almost exclusively in patients with a pre-treatment history of AU (data not shown). The incidence rates of AU-flares were higher for SEC and ETN compared to ADA and IFX, in the analyses (B, C) accommodating for channeling, figure 1 . Compared to ADA, the adjusted HRs of a first on-treatment AU-diagnosis were also higher for SEC and ETA, Table 1 . Conclusion: In clinical practice, SEC and ETN are associated with a higher incidence of AU than ADA and INF, suggesting a poorer protective effect of SEC and ETN against AU. These preliminary results should be interpreted in light of pronounced treatment channeling, which was only partly accommodated for. Disclosure of Interests: Ulf Lindström: None declared, Karin Bengtsson: None declared, Tor Olofsson: None declared, Daniela Di Giuseppe: None declared, Bente Glintborg Grant/research support from: Grants from Pfizer, Biogen and Abbvie, Helena Forsblad-d'Elia Grant/research support from: Unrestricted grant from Novartis., Consultant of: Advisory Board Fees from Sandoz, Novartis, and Abbvie, Lennart T.H. Jacobsson Consultant of: AbbVie, Eli Lilly, Janssen, Novartis and Pfizer, Johan Askling Grant/research support from: JA acts or has acted as PI for agreements between Karolinska Institutet and the following entities, mainly in the context of the ARTIS national safety monitoring programme of immunomodulators in rheumatology: Abbvie, BMS, Eli Lilly, Merck, MSD, Pfizer, Roche, Samsung Bioepis, Sanofi, and UCB Pharma